An improved electricity efficiency method based on microcontroller and IoT with infrared sensor - Arif Ainur Rafiq; Sugeng Dwi Riyanto; Ratna Wardani (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2020)
This paper proposes an improved electricity efficiency method using an infrared sensor and internet of things (IoT). Almost all field of human work require electrical energy, especially for household needs. The averages household has many lamps in each room, so if it is not controlled, it will be wasteful of energy. However, this work is carried out to gain a better understanding of a new method for saving energy. The main advantage of this work is the simplification of the sensor used, in which only the infrared sensor required. Although the proposed approach faces numerous challenges, it successfully provides result as parameters that it can be processed rapidly using low-cost microcontrollers. The idea is based on the microcontroller and internet implementation with infrared sensor to monitor the number of people in home to control the lamp light intensity. The idea is proven in two ways: design and experiment. In this paper, the implementation of Raspberry Pi and Arduino is created to monitor the number of people in room and control the lamp intensity through internet or web. Arduino uses for the sensor processing and Raspberry Pi as server. The web is used to display the monitoring result by retrieving data from database that created using MySQL. The result indicates that the electricity bill decreased between 7.7-8.2% over 2 months implementation. The conclusion of this study suggests that the research in this area could be directed toward to be used in saving electricity usage in human life, especially for household.